(untitled) (Nuntius Antiquus, 2019)
The present paper intends to analyze the Christianization of the city of Paris and its growing importance in the Merovingian period. The article begins with an introduction of the context of the Gallo-Roman city and the transformations that happened during the final centuries of the Roman Empire. In the third section, the Merovingian Paris will be examined (6th-7th centuries), specifically its three most important churches. Finally, in the final section of the paper, the process on which Paris, a relatively unimportant city at a regional level until the sixth century, became one of the most important cities in Merovingian Gaul will be explained. The consolidation of the Merovingian royal power and the Christianization of the city were part of the same process.